Expanding the demand-resource model by an anthropo-organizational view: Work resilience and the "little prince" and the "self-accountant" approach - Giuseppe Modarelli; Christian Rainero (Administrative Sciences, 2024)
The authors' intention is to conduct an analysis utilizing a purely conceptual, literary content-based investigation of two hermeneutical dimensions associated with work motivation in the public service sector. Specifically, the study focuses on public school teachers in the Italian context due to the neglected way in which they matured in literary production and the hostile work environment brought about by the numerous reforms in a kind of heterogenesis of ends. Through the use of aphorisms and metaphors, after a literature review, gap identification and a content-based analysis, the authors aim to identify an approach that can anthropologically serve as a synthesis formula for workers who are emotionally and intensely invested in their professional practice. Specifically, this includes professions, including educational ones, that are subjected to high exposure to emotional labor (EL). The authors have identified two dimensions: one oriented towards the concept of gift and the other towards possession for integrating the demand-resource model (DRM). To support this analysis, the seminal research work of Belk will be utilized as a reference in the wide range of literary production on the give-and-take approach, according to Schaufeli and Grant. Furthermore, empirical data from previous research will be used to functionally explain how sense-making, when combined with the dynamics of gift-possession, can act as a factor of resilience for professions that hold significant emotional value. In this way, the authors shape a perspective on the theoretical paradigm toward the performance measurement and management system under the lens of New Public Management reform, considering the grand challenges inherent in the educational area by identifying organizational behavioral levers for justifying high motivation-driven actions in an underestimated job segment. In this way, the greatest contribution lies in the possibility of defining a reference framework to expand the DRM in application to the clarification of the foundations inherent in resilience behaviors implemented by educational professions in the specific reference context. The main result would precisely be the ability of the latter to cope with hostile contexts through the dynamics of gift and possession that promote work resilience through the attribution of meaning and identity to the job. These perspectives are useful for deepening the understanding of performance measurement and management approaches.
Keywords: 350; demand-resource model; emotional labor; organizational behavior; performance measurement and management; sense-making; work motivation